The Bible, Douay-Rheims, Book 46: 2 Machabees : The Challoner Revision (Salt Lake City, UT : Project Gutenberg, 2005)
"The Bible, Douay-Rheims, Book 46: 2 Machabees" is a deuterocanonical book written between 150 and 100 BC. This historical account recounts the persecution of Jews under King Antiochus IV Epiphanes and the Maccabean Revolt led by Judas Maccabeus. Written in Greek by an unknown diaspora Jew, the work chronicles divine interventions and human courage, from the attempted taxation of the Second Temple to the defeat of the Seleucid general Nicanor in 161 BC, culminating in the establishment of the Feast of Dedication. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/2_Maccabees
Release date is 2005-06-01
This eBook was produced by David Widger from etext #1581 prepared by Dennis McCarthy, Atlanta, Georgia and Tad Book, student, Pontifical North American College, Rome
Keywords: Bible. Apocrypha. Maccabees, 2nd